Review of dietary supplements for the management of osteoarthritis in dogs in studies from 2004 to 2014. Issue 1 (23rd July 2015) - Comblain, F.; Serisier, S.; Barthelemy, N.; Balligand, M.; Henrotin, Y.
Abstract : Osteoarthritis (OA) is a chronic, painful, degenerative and inflammatory disease that affects the synovial joints and leads finally to the loss of mobility. It is highly prevalent in dogs. Nowadays, no cure exists, and the pharmacological treatment is limited to clinical signs alleviation. Some positive beneficial effects have been highlighted with dietary supplements in the course of dog OA. The goals of this narrative review are to summarize the scientific data available in the literature on dietary supplements assessed in dog OA and to discuss some trails about how to improve several aspects of research and issues with dietary supplements, such as bioavailability and dosage regimen. Chondroitin sulphate, glucosamine, undenaturated type II collagen, avocado–soya bean unsaponifiables, curcumin and polyunsaturated fatty acids were studied in dog OA and therefore discussed in the present review. Most of them showed anticatabolic and anti‐inflammatory effects. Unfortunately, few data exist concerning their pharmacokinetics. Their bioavailability is low, but new formulations are developed to enhance their gastrointestinal absorption. The clinical relevance of these new formulations compared to native forms should be demonstrated in good clinical trials. Even if further investigations are needed, dietary supplements should be considered in OA management.